Morphophysiological biometry and grain production in cowpea under different phosphorus levels - Bezerra, Antonio Aécio de Carvalho; Costa Filho, Raimundo Soares da; Oliveira, Simone Raquel Mendes de; Freire Filho, Francisco Rodrigues (Comunicata Scientiae, 2018)
In tropical and semi-arid regions of Brazil, phosphorus is one of the most limiting elements of cowpea productivity. The aim of this study was to assess the effects of applying five phosphorus doses in the soil on morpho-physiological and production components in three improved cultivars of cowpea. The experiment was carried out at the São Fernando farm located in José de Freitas, PI, Brazil, in a Plinthosol with a low phosphorus content. The experimental design was complete randomized block design with four replications in a 5 × 3 factorial scheme consisting of five phosphorus doses (0, 60, 120, 180, and 240 kg P2O5 ha−1) and three improved cowpea cultivars (BRS Guariba, BRS Tumucumaque, and BRS Cauamé). No interaction was observed between cultivars and phosphorus doses for any of the assessed variables. The cultivar BRS Tumucumaque showed the highest value for one-hundred-grain weight (21.0 g) and, together with BRS Guariba, the highest value of pod length. An increment was observed in growth (stem diameter, main branch length, leaf area, and shoot dry matter) and production characteristics (number of pods per plant, number of grains per pod, one-hundred-grain weight, and grain production per plant) in response to increases in phosphorus doses. The dose of 183.1 kg P2O5 ha−1 provided the maximum technical grain yield, estimated at 2,023.3 kg ha−1.